Evaluation of the Effect of a Clobetasol Propionate and Nystatin Mouthwash on Recurrent Aphthous Stomataitis - A. Darbandi; A. Ganbari (Tehran University of Medical Sciences, 2006)
Statement of problem: Recurrent aphthous stomatitis (RAS) is one of the most common diseases affecting human oral mucosa. The etiology of this disease remains unclear; therefore a definitive treatment has not yet been established and corticosteroids might be prescribed to reduce the symptoms associated with RAS. Purpose: The aim of this study was to determine the effects of a mouthwash containing 0.05% clobetasol and nystatin on aphthous ulcers. Materials and Methods: Forty patients with RAS, 18 males and 22 females with an age range of 11-50 years, participated in this double-blind placebo-controlled clinical trial. The subjects were randomly divided into two equal groups. Group A received a mouthwash containing 0.05% clobetasol and 100,000 IU/cc nystatin with instructions to rinse with 20 drops for 5 minutes, 3 times daily. Group B (control) received placebo and was asked to follow the same instructions. All symptoms along with possible adverse effects were measured and recorded during the 2-week study period. Statistical analysis was performed using chi-square and independent paired t-tests. Results: Complete resolution of the lesions and their symptoms was observed in 85% of the participants in group A. Two (10%) patients showed no response to treatment and the symptoms increased in 5% (1 patient). There were no measurable changes in pain or healing time of the ulcers in the control group. Conclusion: The use of the tested mouthwash was found to be a safe and efficacious treatment for RAS of the oral mucosa.